Application of Mathcad Program in Solving Conditional Extremum Problem - Nilufar Mirzamaxmudova (Web of Journals Publishing, 2023)
The issue of conditional extremum plays an important role in solving technical and technological issues. There are different ways to solve this type of problem. This article shows methods for solving the conditional extremum in the MathCAD software package. Solving problems in this way emphasizes that with the help of information technology, calculations can be facilitated.